Convergence and divergence of mental health symptoms among adolescents and their friends - Delfina Bilello; Chloe Bracegirdle; Jack L. Andrews (European Child & Adolescent Psychiatry, 2026)
Abstract Peers play a central role in shaping adolescent mental health, with internalising and externalising symptoms often clustering within friendship groups. In this study we examined whether adolescents’ internalising and externalising symptoms converged, or diverged, with their best friend(s) symptoms over time, and whether gender and experiences of victimisation influenced these patterns. We conducted secondary data analysis of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU), using two waves collected in Sweden and Germany, comprising a total of 5705 participants (54% boys and 46% girls aged M = 14.89, SD = 0.66). Cross-sectionally, adolescents’ internalising and externalising symptoms were positively associated with those of their best friend(s) at both timepoints. Longitudinally, adolescents, on average, significantly diverged from their best friend(s) in internalising symptoms over time. Yet, girls, but not boys, showed convergence in externalising symptoms with their friendship group over time. Victimisation was associated with greater symptom dissimilarity among best friend(s) but did not impact average longitudinal convergence or divergence over time. Exploratory analyses identified friendship stability as a driver of symptom convergence. This study highlights individual variability in adolescents’ tendency to align with their peers, underscoring the importance of identifying underlying mechanisms. Results are discussed in the context of identity formation during adolescence.